Cardiac outcomes in patients with acute coronary syndrome attributable to calcified nodule. (February 2021) - Sugane, Hiroki; Kataoka, Yu; Otsuka, Fumiyuki; Nakaoku, Yuriko; Nishimura, Kunihiro; Nakano, Hiroki; Murai, Kota; Honda, Satoshi; Hosoda, Hayato; Matama, Hideo; Doi, Takahito; Nakashima, Takahiro; et al.
Abstract: Background and aims: Calcified nodule (CN) is an eruptive calcified mass causing acute coronary syndrome (ACS). Since coronary calcification is associated with an elevated cardiac event's risk, ACS attributable to CN may exhibit worse clinical outcome following percutaneous coronary intervention (PCI). Methods: We retrospectively analyzed 657 ACS patients receiving PCI with newer-generation drug-eluting stent (DES) implantation under intravascular ultrasound (IVUS) guidance. CN was defined as (1) protruding calcification with its irregular surface and (2) the presence of calcification at adjacent proximal and distal segments. The primary endpoint was a composite of major adverse cardiac event [MACE = cardiac death + ACS recurrence + target lesion revascularization (TLR)]. Results: CN was identified in 5.3% (=35/657) of the study subjects. CN patients were more likely to have coronary risk factors including hypertension ( p  = 0.005), chronic kidney disease ( p  < 0.001), maintenance hemodialysis ( p  < 0.001) and a history of PCI ( p  < 0.001). During the observational period (median = 1304 days), CN was associated with an increased risk of MACE (HR = 7.68, 95%CI = 4.61–12.80, p  < 0.001), ACS recurrence (HR = 12.32, 95%CI = 6.05–25.11, p  < 0.001) and TLR (HR = 10.48, 95%CI = 5.80–18.94, p  < 0.001). These cardiac risks related to CN were consistently observed by Cox proportional hazards model (MACE: p < 0.001, ACS recurrence: p  < 0.001, TLR: p  < 0.001) and a propensity score–matched cohort analysis (MACE: p  = 0.002, ACS recurrence: p  = 0.01, TLR: p  = 0.005). Of note, over 80% of TLR at the CN lesion was driven by its re-appearance within the implanted DES. Conclusions: ACS patients attributable to CN have an increased risk of ACS recurrence and TLR, mainly driven by the continuous growth and protrusion of the calcified mass. Graphical abstract: Image 1 Highlights: Acute coronary syndrome (ACS) patients attributable to calcified nodule (CN) exhibited significant heightened risk of adverse cardiac events compared to those without. In ACS patients attributable to calcified nodule, recurrence of ACS occurred mainly due to in-stent restenosis. Over 80% of in-stent restenosis at lesions containing CN exhibited its re-appearance within the implanted stent. . Our findings suggest the need for additional therapeutic approach to modify CN in ACS subjects. .